Polar Integers and Polar Integer Optimization - Shipilevsky, Yuly (Statistics, Optimization & Information Computing, 2022)
This is a pioneering work, introducing a special class of complex numbers, wherein their absolute values and arguments given in a Polar coordinate system are integers, which when considered within the complex plane, constitute Unicentered Radial Lattice and similarly for quaternions and Euclidean R2 and R3 Spaces. The corresponding Optimization Problems are introduced as well.